Pelaksanaan Penuntutan Oditur Militer Terhadap Oknum Tentara Nasional Indonesia Angkatan Darat (TNI AD) dalam Tindak Pidana Umum - fajri, al (Law, Development and Justice Review, 2024)
This research is aimed at finding out more about the implementation of prosecutions by Military Prosecutors starting from the case files resulting from the investigation being received by the Military Prosecutor until the transfer of case files to the Military Court. The aim of this research is to determine the implementation of prosecutions carried out by Military Prosecutors against TNI AD personnel who commit criminal acts and to find out what the obstacles are and how to overcome obstacles in carrying out prosecutions against TNI AD individuals who commit criminal acts. This type of research is a field research located at the I-04 Military Prosecutor's office, Padang, West Sumatra. The data used are primary data and secondary data obtained from interviews, statutory regulations and literature studies. The informant in this research was the Head of the I-04 Padang Military Authority. The results of this research are that the implementation of the prosecution begins when the case file is received by the Oditur, the Oditur examines the case file, makes a Sph Father, makes an indictment, and transfers the case file to the Military Court.